Analysis of the Influence of Prior Experience & Product Knowledge on the Decision to Make Brand Switching Mediated by Satisfaction in Purchasing Adventure Motorcycles - Hasan, Muhamad Fuat; Utami, Sasi; Laely, Nur; Marwanto, IGG Heru (Islamic University of Kalimantan MAB Banjarmasin, 2024)
This study aims to ascertain and evaluate the Prior Influence of Experience, Product Knowledge, and Satisfaction on Consumer Decisions Performing Brand Switching in Purchasing Motor Adventure Products. Technique Sampling is determined by purposive sampling, where there are criteria respondents, but it also uses the accidental method of determining the sample based on coincidence where anyone happens to meet the researcher which can be used as a sample by distributing questionnaires to members of the adventure motorcycle community The analytical technique applied is the descriptive analysis technique, Partial Last Square (PLS) statistical analysis method for looking for inner models, outer models, and hypotheses. The results of this study show acceptance of the entire hypothesis, namely the existence of a noteworthy and favorable influence on prior experience (X1), product knowledge (X2), and satisfaction factors (X3) on Consumer Decisions to Brand Switching in Purchasing Motorcycle Adventure Products.